To find the zeroes of the function \( f(x) = 2x^2 + 5x - 3 \), we need to solve the equation \( 2x^2 + 5x - 3 = 0 \).
We can use the quadratic formula:
\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]
Here, \( a = 2 \), \( b = 5 \), and \( c = -3 \).
First, we calculate the discriminant:
\[ b^2 - 4ac = 5^2 - 4(2)(-3) = 25 + 24 = 49 \]
Now, we can use the quadratic formula:
\[ x = \frac{-5 \pm \sqrt{49}}{2 \cdot 2} = \frac{-5 \pm 7}{4} \]
Calculating the two potential solutions:
-
\( x = \frac{-5 + 7}{4} = \frac{2}{4} = \frac{1}{2} \)
-
\( x = \frac{-5 - 7}{4} = \frac{-12}{4} = -3 \)
Thus, the roots (or zeroes) of the function are:
\[ x = \frac{1}{2}, \quad x = -3 \]
Based on the responses provided, the correct answer is:
x equals one half; x equals negative 3.